The Effect of Wordwall Application Toward Students' Vocabulary Mastery (A Quasi Experimental at the Seventh Grade Students of SMPN 15 Bengkulu City, Academic Year 2025-2026) - Anita Jufriani; Ali Akbar Jono; Pebri Prandika Putra (The Future of Education Journal, 2026)
This study aimed to determine the effect of using Wordwall as a learning medium on the vocabulary mastery of seventh-grade students. This study used a quasi-experimental design with a nonequivalent control group design, involving an experimental class and a control class. Data were collected through pre-test and post-test. The results showed an increase in vocabulary scores in both classes, but the increase in the experimental class was greater. The test results showed a significant difference between the experimental and control classes, with a p-value of 0.033 < 0.05. Effect size analysis showed a Partial Eta Squared value of 0.114, which is included in the moderate effect category. Thus, it can be concluded that the use of Wordwall as a learning medium has a significant effect on seventh-grade students' vocabulary mastery.